Rheology of natural hydraulic lime grouts for conservation of stone masonry-influence of compositional and processing parameters - Baltazar, Luis G. (2019)
This work is funded by National Funds through Portuguese Foundation for Science and Technology (FCT/MCTES), Reference UID/CTM/50025/2013 and Fundo Europeu de Desenvolvimento Regional (FEDER) funds through the COMPETE 2020 Programme under the project number POCI-01-0145-FEDER-007688.